2011
DOI: 10.1016/j.socscimed.2011.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stressors, low well-being, smoking, and alcohol use among South African adolescents

Abstract: This is the first study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 45 publications
2
30
1
2
Order By: Relevance
“…[6] It has also been found that SA individuals who have high levels of psychological stress do not partake in physical exercise, and engage in poor behavioural patterns (such as alcohol consumption, smoking and drug abuse) because of an inability to cope with the high levels of perceived stress. [7] Poor behavioural patterns in conjunction with decreased physical activity levels can lead to increases in perceived stress and manifestation of chronic disease conditions, which are currently increasing rapidly in the SA population. [8] The increased prevalence of stress-related disease indicates a need for improved stress management, such as the use of the psychological technique of cognitive behavioural therapy.…”
mentioning
confidence: 99%
“…[6] It has also been found that SA individuals who have high levels of psychological stress do not partake in physical exercise, and engage in poor behavioural patterns (such as alcohol consumption, smoking and drug abuse) because of an inability to cope with the high levels of perceived stress. [7] Poor behavioural patterns in conjunction with decreased physical activity levels can lead to increases in perceived stress and manifestation of chronic disease conditions, which are currently increasing rapidly in the SA population. [8] The increased prevalence of stress-related disease indicates a need for improved stress management, such as the use of the psychological technique of cognitive behavioural therapy.…”
mentioning
confidence: 99%
“…Thus, the prevalence of alcoholism in adolescents varies from 16.7% in Tanzania [9] to 55.5% in Gabon [7]; and the smoking of 10.6% in South Africa [6] to 21% in Gabon [7]. In South Africa, these addictions among adolescents had correlate with crime, cardiovascular diseases, and cancer [1]. In Congo, the law banning smoking in and around schools was adopted, to reduce tobacco-related diseases [10].…”
mentioning
confidence: 54%
“…The high social status was defined by occupation and salary of parents. EAI was define for use at least once a week, and CS by frequent use in the past 30 days [1].…”
Section: Definitionsmentioning
confidence: 99%
“…A par das atitudes e comportamentos dos pais e familiares face ao consumo, as atitudes e comportamentos dos grupos de pares face a bebidas alcoólicas são os fatores de risco mais frequentemente referidos na literatura como fortemente associados ao consumo de álcool (Zarzar, et al, 2012;Svensson, 2010;Bekman, Cummings & Brown, 2010). A disponibilidade financeira, ou o dinheiro disponível para despesas pessoais, embora menos referida pela literatura, surge igualmente como fator de risco para o consumo (Donath et al, 2012).Embora no presente estudo o prazer decorrente do consumo de bebidas alcoólicas tenha sido identificado por todos os grupos enquanto fator de risco para o consumo regular, o mesmo raramente é referido pela literatura.…”
Section: Discussionunclassified
“…De salientar ainda que, tal como referido na literatura, os dados apontam no sentido de o consumo de álcool entre os jovens servir a gestão de emoções negativas perante as quais não têm estratégias emocionais e cognitivas para lidar (Chartier, Hesselbrock & Hesselbrock, 2010;Schulte, Ramo & Brown, 2009).No que respeita às diferenças de género, a "baixa autoestima" enquanto fator de risco para o consumo regular de álcool, foi unicamente identificado pelo grupo feminino, sugerindo que mais frequentemente o consumo de álcool possa ser utilizado pelas raparigas como forma de aumentar a autoconfiança, comparativamente com os rapazes. A facilidade de acesso a bebidas alcoólicas enquanto fator de risco para o consumo foi identificada unicamente pelo grupo misto como fator de risco para o consumo regular, sendo contudo um fator frequentemente presente na literatura (Kuntsche, Rehm, & Gmel, 2004;Brook, et al, 2011).…”
Section: Discussionunclassified